Assessment of Rhizospheric Streptomyces Strains as Potential Biopesticides for Further Applications on Wheat Crops - Wiem Alloun; Hadjer Kecis; Noreddine Kacem Chaouche (Biology and Life Sciences Forum)
Actinobacteria species, especially Streptomyces, are well known and widely studied as promising biocontrol and phytostimulation agents. They constitute an eco-friendly substitute for chemical fungicides. Streptomyces-like strains were isolated from wheat fields to suppress the growth of Fusarium, the leading wheat root-rot-associated fungi, and to stimulate plant growth. The isolates were characterized morphologically and biochemically and subjected to a comprehensive in vitro screening for various plant-growth-promoting (PGP) traits. The potential beneficial effects of these strains on wheat plants were evaluated upon their inoculation (germination rate, shoot and root lengths). Among 32 isolates, the strain Act 02 was positive in inhibiting Fusarium growth and showing vigorous antifungal activity. In vitro assays demonstrated the ability of Act 02 to produce ammonia and indole-acetic acid (IAA). The strain showed extracellular enzyme production, such as Chitinases, Cellulases, and solubilized phosphate (Ca3PO4). The strain Act 02 tolerated high concentrations of NaCl with a considerable interval of [1–8]% (w/v), with optimum ranges between [1–3]%. 16s RNA gene barcoding and phylogenetic analysis showed that the strain Act 02 belongs to S. lividans with a 99.04% similarity. Seed germination and pot experiments were conducted by inoculating Triticum durum seeds with a selected isolate extract. Act 02 was able to significantly increase plant lengths.